Circumcising human subjects: An evaluation of experimental foreskin amputation using the Declaration of Helsinki. (9th January 2019) - Drash, Michael
Abstract: This paper explores ethical considerations for active studies of circumcision, i.e., the amputation of the foreskin, in the form of a case study of three major trials performed in African countries in the early 2000s. The paper outlines the function of the foreskin and method and history of its amputation as well as its current use in attempting to combat the global AIDS crisis. These trials are then interrogated in accordance with the Declaration of Helsinki. In particular, the irreversible nature of amputation is given great consideration. The case studies are found to have serious failures in terms of the modern iteration of the Declaration of Helsinki. This paper calls for extreme scrutiny in accordance with international norms relating to the ethical treatment of human subjects in a research context of studies of circumcision if and when they are proposed again.